Formation needs of certified and noncertified public school teachers of english at 7th,8th, and 9th grades of basic education in San Salvador, El Salvador, 2001-2011 - Vásquez Cortez, Samuel
The current state of in-service formation of public school teachers of English at 7th, 8th, and 9th grades of basic education in San Salvador, El Salvador, is an issue that deserves particular and better attention than it is nowadays receiving. It is an area with a number of significant problems that affect the students’ English language learning. Some of the most substantial constraints are: 1) the large number of teachers of English who are actually teaching English without appropriate and required professional qualifications and training, 2) the lack of diagnostic and research results to support the design and the execution of the training courses, 3) the unsequent, insufficient and inappropriate design of the teachers continuing preparation process, and 4) the lack of sustainability of the same.